(untitled) - Dyer, Jeff (Boston, Mass., 2011)
Some people are just natural innovators, right? With no apparent effort, they discover ideas for new products, services, and entire businesses. It may look like innovators are born, not made. But according to Jeffrey Dyer and Hal Gregersen, anyone can become more innovative. How? Master the discovery skills that distinguish innovative entrepreneurs and executives from ordinary managers. In The Innovator's DNA, the authors identify five capabilities demonstrated by the best innovators: ʺ Associating: drawing connections between questions, problems, or ideas from unrelated fields ʺ Questioning: posing queries that challenge common wisdom ʺ Observing: scrutinizing the behavior of customers, suppliers, and competitors to identify new ways of doing things ʺ Experimenting: constructing interactive experiences and provoking unorthodox responses to see what insights emerge ʺ Networking: meeting people with different ideas and perspectives The authors explain how to generate ideas with these skills, collaborate with "delivery-driven" colleagues to implement ideas, and build innovation skills throughout your organization to sharpen its competitive edge. They also provide a self-assessment for rating your own innovator's DNA. Practical and provocative, this book is an essential resource for all teams seeking to strengthen their innovative prowess
Keywords: Sáng tạo trong kinh doanh,Creative ability in business